Online discontent: comparing Western European far-right groups on Facebook. Issue 4 (8th August 2019) - Klein, Ofra; Muis, Jasper
ABSTRACT: Far-right groups increasingly use social media to interact with other groups and reach their followers. Social media also enable 'ordinary' people to participate in online discussions and shape political discourse. This study compares the networks and discourses of Facebook pages of Western European far-right parties, movements and communities. Network analyses of pages indicate that the form of far-right mobilization is shaped by political opportunities. The absence of a strong far-right party offline seems to be reflected in an online network in which non-institutionalized groups are the most prominent actors, rather than political parties. In its turn, the discourse is shaped by the type of actor. Content analyses of comments of followers show that parties address the political establishment more often than immigration and Islam, compared to non-institutionalized groups. Furthermore, parties apply less extreme discursive practices towards 'the other' than non-institutionalized groups.